2000
DOI: 10.1175/1520-0434(2000)015<0349:atbmjs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Betts–Miller–Janjic Scheme of Convection in Prediction of the Indian Monsoon

Abstract: The performance of the Betts-Miller-Janjic scheme of convection has been investigated for prediction of the Indian monsoons. For this purpose a limited area numerical weather prediction model with two schemes of convection, one with the Betts-Miller scheme and other with the Betts-Miller-Janjic scheme, is run for five cases of monsoon depression that made landfall over the Indian coast. The results from the two schemes are compared. Detailed analyses of mean sea level pressure, wind, and rainfall have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
(3 reference statements)
0
16
0
Order By: Relevance
“…In addition, the latest and most exhaustive study discussing the performance of WRF for tropical cyclone prediction in the Bay of Bengal [Srinivas et al, 2013b] shows that, at 9 km resolution, the KF scheme provides the best simulations for intensity and track prediction, giving higher convective warming with stronger vertical motions relative to the other tested cumulus schemes. Vaidya and Singh [2000], Mukhopadhyay et al [2010], and Srinivas et al [2013a] on the other hand illustrated that the BMJ scheme produces the most reasonable mean monsoon pattern, with realistic atmospheric flow, surface pressure, heating profiles, and moist instability.…”
Section: Model Experiments and Data Setsmentioning
confidence: 95%
“…In addition, the latest and most exhaustive study discussing the performance of WRF for tropical cyclone prediction in the Bay of Bengal [Srinivas et al, 2013b] shows that, at 9 km resolution, the KF scheme provides the best simulations for intensity and track prediction, giving higher convective warming with stronger vertical motions relative to the other tested cumulus schemes. Vaidya and Singh [2000], Mukhopadhyay et al [2010], and Srinivas et al [2013a] on the other hand illustrated that the BMJ scheme produces the most reasonable mean monsoon pattern, with realistic atmospheric flow, surface pressure, heating profiles, and moist instability.…”
Section: Model Experiments and Data Setsmentioning
confidence: 95%
“…Some possible factors that could contribute would be that local boundary formulation in MYJ may be more appropriately capturing the vertical environment in the complex terrain compared to the non-local YSU scheme which seeks to simulate vertical mixing and boundary layer evolution using averaged and grid representative fields. With regard to the BMJ CU emerging in the top configuration, there are a number of studies for the ISMR where it has emerged as performing "overall best" (Vaidya and Singh, 2000;Ratnam and Kumar, 2005;Vaidya, 2006;Rao et al, 2007;Kumar et al, 2010;Mukhopadhyay et al, 2010;Srinivas et al, 2013;Sikder and Hossain, 2016). As for the MP scheme, there are limited studies in comparison to those that have studied the CU configuration for the ISMR.…”
Section: Model Configuration and Experimental Setupmentioning
confidence: 99%
“…The Betts-Miller-Janjic Cumulus parameterization scheme was used because it is well tested for regional application and precipitation forecasting (Vaidya and Singh, 2000). Gilliland and Rowe (2007) found that it considers a sophisticated cloud mixing scheme in order to determine entrainment/detrainment which is found to be more suitable for non-tropical convection.…”
Section: Weather Research and Forecasting (Wrf) Modelmentioning
confidence: 99%